Craving on the move: targeting smoking memories with a novel 3MDR–smoking cessation protocol - Annel P. Koomen; Anne Marije Kaag; Kees A. M. Jongenelen; Rianne Wouters; Hein J. F. van Marle; Hein J. F. van Marle; Hein J. F. van Marle; Hein J. F. van Marle; Odile A. van den Heuvel; Odile A. van den Heuvel; Odile A. van den Heuvel; Ysbrand D. van der Werf; et al. (Frontiers in Psychiatry)
IntroductionImproved effectiveness and treatment adherence is needed in smoking cessation (SC) therapies. Another important challenge is to disrupt maladaptive drug-related memories. To achieve these goals, we developed a novel treatment strategy on the basis of motion-assisted memory desensitization and reprocessing (3MDR).MethodsIn this study, the added effect of a distractor task following memory recall during a newly designed 3-day SC version of 3MDR (3MDR-SC) protocol on reducing smoking cue–elicited craving was investigated in abstinent chronic smokers. Chronic smokers were randomly allocated to an active 3MDR-SC group (receiving 3MDR-SC with a working memory distractor task) (n = 42) or a control 3MDR-SC group (receiving 3MDR-SC with a non-distracting task) (n = 39). Smoking cue–induced craving and physiological measures were assessed at baseline (T0) and 1 day after the intervention (T4), and smoking behavior was measured at T0 and 2-week (FU1) and 3-month (FU2) follow-up.ResultsSignificant decreases in cue-induced craving from T0 to T4 and daily cigarette use from T0 to FU1 and FU2 were observed but not differ between the two experimental groups. Cue-induced changes in heart-rate variability and skin conductance, which did not differ from T0 to T4, and relapse at FU2 were also not different between groups. Dropout rate during intervention was 2.5%.ConclusionsThe 3-day 3MDR-SC intervention resulted in a reduction in cue-induced craving and smoking behavior and showed very good treatment adherence. There was no added effect of the distractor task on 3MDR-SC efficacy. Further studies, including a treatment as usual control, are needed to confirm 3MDR-SC as an effective SC therapy.